1999
DOI: 10.1136/gut.45.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Strictures in Crohn’s disease are characterised by an accumulation of mast cells colocalised with laminin but not with fibronectin or vitronectin

Abstract: Background/Aims-Intestinal fibrosis and stricture formation is an unresolved problem in Crohn's disease. The aim of this study was to investigate whether mast cells accumulate in these tissues and whether their localisation is associated with extracellular matrix components. (Gut 1999;45:210-217) Methods-Mast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
99
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 30 publications
4
99
0
Order By: Relevance
“…Studies in mast cell-deficient mice suggest that tissue mast cells do not mediate the response of murine intestinal muscle to TNBS-induced inflammation (5). Although tissue mast cell numbers are decreased during the inflammatory response to TNBS and in Crohn's disease generally (19,22,27), an increase in mast cells in the submucosa and both circular and longitudinal smooth muscle layers is seen during the chronic, fibrotic response to TNBS and in the strictures of human Crohn's disease patients suggesting mast cells play a role in tissue fibrosis (6,23,31). During the course of chronic inflammation induced by TNBS in the mouse and in other models of colitis, a sequential pattern of immunological response is observed (1,3,4).…”
Section: Discussionmentioning
confidence: 98%
“…Studies in mast cell-deficient mice suggest that tissue mast cells do not mediate the response of murine intestinal muscle to TNBS-induced inflammation (5). Although tissue mast cell numbers are decreased during the inflammatory response to TNBS and in Crohn's disease generally (19,22,27), an increase in mast cells in the submucosa and both circular and longitudinal smooth muscle layers is seen during the chronic, fibrotic response to TNBS and in the strictures of human Crohn's disease patients suggesting mast cells play a role in tissue fibrosis (6,23,31). During the course of chronic inflammation induced by TNBS in the mouse and in other models of colitis, a sequential pattern of immunological response is observed (1,3,4).…”
Section: Discussionmentioning
confidence: 98%
“…For example, we showed that experimental inflammatory arthritis was significantly attenuated in 6 − /7 − B6 mice and 6 − /7 + B6 mice relative to 6 + /7 − B6 mice (11,12). Increased numbers of hTryptase-β + MCs have been detected in intestinal specimens from patients with ulcerative colitis (UC) and Crohn disease (13). Colorectal biopsies from UC patients also constitutively released significantly more immunoreactive hTryptase-β into the conditioned medium than did colorectal biopsies from normal individuals (14).…”
mentioning
confidence: 94%
“…On this point, a recent paper has shown that, beside type 2 lymphocytes, mucosal mast cells are also a significant source of IL-5 in Crohn disease (26). This is particularly relevant when considering the mucosal infiltration with mast cells (27) as well as their activation even in quiescent Crohn disease (2,28). Such an impact of mast cells on mucosal eosinophil migration has already been suggested in asthma (29).…”
Section: Discussionmentioning
confidence: 99%